The Effect of Vitamin C Administration on Hemoglobin and Hematocrit of Albino Rats (Rattus norvegicus) - Damayanti, Ratna; Firdhausia, Hasna; Ainaya, Deninda; Kha, Khansa; Nisrina, Naila; Pahlevi, Annisa Cahya Reza; Syafira, Shela; Alfarizi, Alifian (Universitas Airlangga, 2025)
Anemia, a condition characterized by low hemoglobin or red blood cell levels, is a widespread nutritional issue affecting over 2 billion people globally. Iron deficiency, folic acid, and vitamin B12 or C deficiencies are common causes, with vitamin C playing a crucial role in enhancing iron absorption. This study aimed to investigate the impact of various doses of vitamin C supplementation on hematocrit and hemoglobin levels in rats. The experiment employed a True Experimental design with a control group and three treatment groups receiving different doses of vitamin C (1 mg/ml, 3 mg/ml, and 6 mg/ml) over three weeks. Results showed no significant increase in hemoglobin or hematocrit levels across treatment groups compared to the control. Although some variations were observed in the data, particularly with the 6 mg/ml dose showing a slight decrease in hemoglobin levels, the overall effect of vitamin C on these hematological parameters was not substantial. These findings suggest that animal health, feed quality, and vitamin C administration duration influence the outcomes.